Research on high school students’ behavior in art course within a virtual learning environment based on SVVR - Wang, Hongya; Li, Dongning; Gu, Chao; Wei, Wei; Chen, Jiangjie (Frontiers in Psychology, 2023)
Introduction Students who use spherical video-based virtual reality (SVVR) teaching materials for learning are able to gain more self-regulated, explorative, and immersive experiences in a virtual environment. Using SVVR teaching materials in art courses can present diverse and unique teaching effects, while also leading to the emergence of students’ flow states. Methods Therefore, through an art course teaching experiment, this study investigated 380 high school students and used structural equation modeling to analyze the antecedents and outcomes of students’ flow state in using SVVR teaching materials. Results The results show that in using SVVR teaching materials in art courses, more attention should be paid to the control and telepresence in the antecedents of students’ flow state. Discussion Only when they obtain better flow experiences can they have higher perceived usefulness and satisfaction with the content of the art course, as well as stronger intentions to continue using it. These results can provide a reference for the development and use of SVVR teaching materials in high school art courses.